PERCEPTION OF RESIDENTS IN RESIDENTIAL HIGH-RISE BUILDINGS IN TERM OF SUSTAINABILITY IN ERBIL CITY - BAIZ, WEZHA HAWEZ; HOSKARA, ERCAN (Journal of Duhok University, 2021)
Land price, global icon, and rising population are among the obvious factors to encourage mega structures in Erbil city. Consequently, high-rise and tall buildings have developed and spread in various ways in the city and living in apartments is currently a lifestyle phenomenon. The main purpose of this paper is to investigate the high-rise residential satisfaction. Through it, those factors have affected on the satisfaction level of residences in residential high-rise buildings of a subset of subjects are analysed in the elected two residential high-rise buildings in the city. The background, through literature review, focuses on determinants sustainability that have an impact on residential satisfaction as the design of the units, building material qualities, security and safety, confidentiality and privacy, socio-cultural aspects, and community. In another word, this study focuses on the sustainable indicators in high-rise residential buildings. The main method for understanding the perception of residents is questionnaires, which related to the apartment, the building, and the surrounding area, with between 18 and 80 years of age in the sample population. The findings demonstrated general significant factors of satisfaction in the high-rises as architectural designs of apartments, space arrangement, and facilities.